Algae as New Kids in the Beneficial Plant Microbiome - Lee, Sang-Moo; Ryu, Choong-Min (Frontiers in Plant Science, 2021)
Previously, algae were recognized as small prokaryotic and eukaryotic organisms found only in aquatic habitats. However, according to a recent paradigm shift, algae are considered ubiquitous organisms, occurring in plant tissues as well as in soil. Accumulating evidence suggests that algae represent a member of the plant microbiome. New results indicate that plants respond to algae and activate related downstream signaling pathways. Application of algae has beneficial effects on plant health, such as plant growth promotion and disease control. Although accumulating evidence suggests that secreted compounds and cell wall components of algae induce physiological and structural changes in plants that protect against biotic and abiotic stresses, knowledge of the underlying mechanisms and algal determinants is limited. In this review, we discuss recent studies on this topic, and highlight the bioprotectant and biostimulant roles of algae as a new member of the plant beneficial microbiome for crop improvement.